Effects of Secreted Mast Cell Mediators on Retinal Pigment Epithelial Cells: Focus on Mast Cell Tryptase - Rei Arai; Ayumi Usui-Ouchi; Yosuke Ito; Keitaro Mashimo; Akira Murakami; Nobuyuki Ebihara (Hindawi Limited, 2017)
Numerous mast cells are present in the choroid, but the effects of mast cell mediators on retinal pigment epithelial (RPE) cells are not well understood. We investigated the influence of mast cell mediators on RPE cells in vitro, focusing on tryptase. Expression of receptors was examined by the reverse transcription polymerase chain reaction. We also assessed production of interleukin 8 and vascular endothelial growth factor (VEGF) after RPE cells were stimulated with mast cell mediators by using an antibody array and enzyme-linked immunosorbent assay. Furthermore, we investigated the influence of tryptase on RPE cell migration and integrity by the scratch assay and the transepithelial resistance. RPE cells expressed protease-activated receptor 2 (PAR2), histamine receptor 1, tumor necrosis factor-α (TNF-α) receptor 1, and CCR 1, 3, 4, 8, and 11. Tryptase, PAR2 agonists, histamine, and TNF-α all enhanced interleukin 8 production by RPE cells, while only tryptase enhanced VEGF production. Tryptase also enhanced expression of phosphorylated extracellular signal-regulated kinases 1/2, resulting in increased migration of RPE cells. However, tryptase did not alter epithelial integrity or the expression of zonula occludens-1 and junctional adhesion molecule-A by RPE cells. Mast cell mediators, especially tryptase, may influence RPE cell inflammation.